Phase I study of vandetanib with radiation therapy with or without cisplatin in locally advanced head and neck squamous cell carcinoma. Issue 3 (16th June 2015) - Papadimitrakopoulou, Vasiliki A.; Frank, Steven J.; Cohen, Ezra W.; Hirsch, Fred R.; Myers, Jeffrey N.; Heymach, John V.; Lin, Heather; Tran, Hai T.; Chen, Changhu R.; Jimeno, Antonio; Nedzi, Lucien; Vasselli, Joseph R.; et al.
Abstract: Background: Vandetanib, added to cisplatin and radiation therapy (RT) overcomes chemoradiation therapy (CRT) and epidermal growth factor receptor (EGFR) inhibitor resistance in head and neck squamous cell carcinoma (HNSCC) lines and models. Methods: Patients with previously untreated HNSCC received vandetanib daily for 14 days (starting dose 100 mg) and then vandetanib + RT (2.2 Gy/day, 5 days/week) for 6 weeks (regimen 1) or vandetanib + RT (2 Gy/day, 5 days/week) + cisplatin (30 mg/m 2 weekly) for 7 weeks (regimen 2). The primary objective was the maximum tolerated dose (MTD) of vandetanib with RT +/‐ cisplatin. Results: Of 33 treated patients, 30 completed therapy (regimen 1, n = 12; regimen 2, n = 18). MTD in regimen 2 was 100 mg (3 dose limiting toxicities [DLTs] at 200 mg), whereas regimen 1 was stopped because of poor recruitment (1 DLT at 200 mg). Most common grade ≥3 adverse events (AEs) were dysphagia (30%), stomatitis (33%), and mucosal inflammation (27%). Five patients discontinued vandetanib because of AEs. Conclusion: Vandetanib with CRT was feasible. © 2015 Wiley Periodicals, Inc. Head Neck 38: 439–447, 2016